2020
DOI: 10.1101/2020.08.28.273110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Refoldability is Pervasive Across theE. coliProteome

Abstract: Decades of research on protein folding have primarily focused on a privileged subset of small proteins that can reversibly refold out of a denaturant. However, these studies are not representative of the complexity of natural proteomes, which consist of many proteins with more sophisticated architectures. Here, we introduce an experimental approach to probe protein refolding for whole proteomes. We accomplish this by first unfolding and refolding E. coli lysates, and then interrogating the resulting protein st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Indeed, the design of Rossmann-like proteins is readily realized compared to P-loops-like proteins with the swapped strand topology ( Romero Romero et al, 2018 ). Furthermore, systematic assays of refoldability of the E. coli proteome, and a comparison of the folds to which these proteins belong, indicated that Rossmann is among the most refoldable folds while P-loop NTPases are among the poorly refolding ones ( To et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the design of Rossmann-like proteins is readily realized compared to P-loops-like proteins with the swapped strand topology ( Romero Romero et al, 2018 ). Furthermore, systematic assays of refoldability of the E. coli proteome, and a comparison of the folds to which these proteins belong, indicated that Rossmann is among the most refoldable folds while P-loop NTPases are among the poorly refolding ones ( To et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by To et al . [182] interrogated the refoldability of the E. coli proteome and found that two-thirds out of approximately 1200 proteins were reversibly refoldable on a biologically relevant timescale of 2 h. This group was enriched with monomeric proteins (75% refoldable), single-domain proteins (70% refoldable), small proteins (less than 20 kDa, 80% refoldable) and proteins without any annotated domains (and hence, more likely to be disordered, 87% refoldable).…”
Section: Refoldabilitymentioning
confidence: 99%
“…These conformations are robustly achieved in vivo via a folding process that involves interactions of the folding chain with molecular chaperones and other maturation factors. The folding process often cannot be reproduced in vitro , in the absence of chaperones and other cellular components 1 5 . However, some small proteins fold spontaneously in vitro in the absence of any other macromolecules 6 .…”
Section: Introductionmentioning
confidence: 99%